Belle Époque: o corpo feminino ditado pela moda e o não corpo retratado por Gustav Klimt em suas obras (ModaPalavra e-periódico, 2010)
This article proposes a discussion on the relationship of Gustav Klimt to the forefront of fashion and its period, through the history of the Belle Époque contextualization and socio-cultural characteristics, the vision of body and its construction at the end of the nineteenth century. Came to the conclusion that the artist has caused, created and contributed to the transformation through his work.
Keywords: Fashion; Belle Époque; Gustav Klim